Poor Survival and Increased Relapsed Rate of Acute Myeloid Leukemia Following Radioactive Iodine Therapy for Papillary Carcinoma of Thyroid - Singh, Ishwor Man; Sah, Bajarang Prasad (Medical Journal of Eastern Nepal, 2025)
Radioactive iodine (RAI) therapy is widely used and has an important role in the management of hyperthyroidism and thyroid malignancies. The development of therapy related acute or chronic leukemia is a very rare complication of RAI therap. Therapy-related acute myeloid leukemia (t-AML) comprises 10–20% of all newly diagnosed cases of AML and is related to previous use of chemotherapy or ionizing radiotherapy for an unrelated malignant non-myeloid disorder or autoimmune disease. We report a case of Papillary Carcinoma of Thyroid who underwent total thyroidectomy followed by treatment with a cumulative dose of 300mCi of RAI later on, developed acute myeloid leukemia after 18 months post therapy. Then after completion of induction and consolidation for AML relapsed after 8 months. Thus suggesting that prognosis for patients with t-AML to be considered worse than that for patients with primary de novo AML which could be due to presence of adverse karyotypic abnormalities and molecular lesions.